Maternity “blues”: prevalence and risk factors - Faisal-cury, Alexandre; Rossi Menezes, Paulo; A Tedesco, Jose Júlio; Kahalle, Soubhi; Zugaib, Marcelo (The Spanish Journal of Psychology, 2008)
Objectives: estimate the prevalence and track the risk factors associated with, Maternity blues (MB). Methods: a transversal study was performed with 113 women, on the tenth day of puerperium. The following instruments were used: Pitt Scale (1968), Stein (1980), Inventory for stressful life events by Holmes & Rahe (1967), and a questionnaire with sociodemographic and obstetric data. Results: the prevalence of MB was 32.7% according to the Stein scale. In the univariated analysis, civil status and tobacco use were associated with MB. Legally married women and nonsmokers showed a risk approximately 4 times lower of experiencing the problem. Conclusions: MB was very prevalent in this sample. Obstetricians must be aware of this condition which may be associated with postpartum depression.